Cocrystal Formation of Betulinic Acid and Ascorbic Acid: Synthesis, Physico-Chemical Assessment, Antioxidant, and Antiproliferative Activity - Nicolov, Mirela; Ghiulai, Roxana M.; Voicu, Mirela; Mioc, Marius; Duse, Adina Octavia; Roman, Roxana; Ambrus, Rita; Zupko, Istvan; Moaca, Elena Alina; Coricovac, Dorina E.; Farcas, Claudia; Racoviceanu, Roxana Marcela; et al. (Frontiers in Chemistry, 2019)
Betulinic acid (BA) was demonstrated to be a very promising anticancer agent against various tumour cell lines such as breast, colon, lung and brain. Despite its strong cytotoxic effect, betulinic acid exhibits low water solubility, feature that is reflected in its poor bioavailability. To overcome these drawbacks, numerous strategies were conducted to improve its physicochemical and pharmacokinetic profile, among which cocrystalization emerged as a promising approach. Thus, our work consisted in obtaining slowly grown cocrystals of BA and ascorbic acid (BA+VitC) in isopropyl alcohol obtained in a hydrothermal experiment. The newly formed cocrystals were characterized by physico-chemical methods such asSEM, DSC, XRPD and FT-IR spectroscopy demonstrating BA+VitC cocrystal formation while their antioxidant activity revealed an additive antioxidant effect. To investigate the biological effect, BA+VitC cocrystals were tested on HaCat (immortalized human keratinocytes), B164A5 and B16F0 (murine melanoma), MCF7 and MDA-MB-231 (human breast cancer) and HeLa (cervical cancer) cell lines. Results of BA upon the tested tumour cell lines, after cocrystallization with vitamin C, indicated a superior cytotoxic effect with the preservation of a good selectivity index assumably due to an improved BA water solubility and consequently an optimized bioavailability.